Analisis Variabel Ekonomi Hijau (Green Economy Variable) Terhadap Pendapatan Indonesia (Tahun 2011-2020) dengan Metode SEM-PLS - Lumbanraja, Penny Chariti; Lumbanraja, Pretty Luci (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2023)
The rapid economic development has the potential to cause negative impacts on the environment. Environmental problems that occur urge policies to implement green economy as the most urgent and effective environmental management tool. This research was conducted by analyzing the issue of implementing a green economy on Indonesia's economic growth. The country's growth by implementing a green economic system is a solution to achieving sustainable country development goals. This research is exploratory in nature using descriptive and inferential analysis techniques. The data used is in the 2011-2020 range (10 years) using the SEM-PLS data analysis technique. From this study it shows that there is a positive and significant influence between the green economy on state income with the result p (0.000) < 0.05 which gives a large effect of 0.965. The influence value of 0.965 means that the implementation of a green economy will make a significant contribution to increasing state revenues in Indonesia. Finally, from the empirical studies conducted, it was found that the country's development must involve a green system in the future with a focus on directions, policies, organizations, areas, capacities, and interventions from all parties as an optimal expansion strategy to achieve Indonesian economic activities that pay attention to environmental conditions.